2012
DOI: 10.1111/j.1759-7714.2011.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B‐cell lymphoma presenting as large anterior chest wall mass involving pleura and lung: A possible result of post‐traumatic chronic inflammation

Abstract: A 67 year-old-man was hospitalized due to chronic pain and a large mass on the anterior chest wall. His medical history showed chest trauma in 1970, the reconstitution of the scenario revealed there was blunt trauma with swelling and rib fracture on the same side. Physical examination revealed an isolated large anterior chest wall mass. Chest radiography showed two bilateral irregular masses, chest computed tomography showed a large right chest wall tumor with pleural effusion, nodules of the right upper lobe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…DLBCL is a group of large, lymphoid B‐cell malignant proliferations that is clinically, morphologically and genetically heterogeneous, constitutes 30% of all NHL and the most common histological subtype; microscopically the cells of DLBCL are large with vesicular nuclei, and prominent nucleoli and immunocytochemically the cells are LCA+, CD20+, CD3‐, BCL2+ and BCL6+ . Chest wall DLBCL/TCRBCL as per our review of literature accounted for 11 of 20 (55.0%) of cases . We did not diagnose any DLBCL as such by FNA cytology in our material, but our cytologically diagnosed centroblastic lymphoma cases (two of 10 NHL) proved to be DLBCL histologically.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…DLBCL is a group of large, lymphoid B‐cell malignant proliferations that is clinically, morphologically and genetically heterogeneous, constitutes 30% of all NHL and the most common histological subtype; microscopically the cells of DLBCL are large with vesicular nuclei, and prominent nucleoli and immunocytochemically the cells are LCA+, CD20+, CD3‐, BCL2+ and BCL6+ . Chest wall DLBCL/TCRBCL as per our review of literature accounted for 11 of 20 (55.0%) of cases . We did not diagnose any DLBCL as such by FNA cytology in our material, but our cytologically diagnosed centroblastic lymphoma cases (two of 10 NHL) proved to be DLBCL histologically.…”
Section: Discussionmentioning
confidence: 86%
“…Review of literature corresponding to our 15‐year study period (2000‐2015) revealed 20 reports based either on cases series or isolated cases (Table ) in which 26 histologically confirmed chest wall lymphoma cases were described . Location of the swellings was the anterior chest wall/manubrium in 14 cases, left chest wall (four cases), right chest wall (three cases), lateral chest wall (NOS in two cases), back in one case and rib/chest wall swellings and NOS in two cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could then lead to lymphomagenesis, as seen in PAL. Fouad et al [19] reported the case of another patient with DLBCL that developed in the chest wall. The patient had a history of blunt trauma with swelling and rib fracture, 41 years prior.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presentation of PPL is minor non-specific symptoms, such as persistent cough, or maybe asymptomatic in up to one half of the cases ( 7 ). Radiographic findings of PPL are not specific, but the typical presentations are single or multiple nodular shadows that may involve one or both lungs, these well-defined infiltrations frequently have air-bronchograms ( 5 , 8 , 9 ), and the nodal involvement in about 30% of the cases is detectable ( 9 ). Less than 10% of the patients have bilateral diffuse ill-defined infiltrations along the bronchovascular pattern and interlobular septa, which have reticulonodular opacities, and atelectasis or pleural effusion are rarely seen ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%